Pengaruh Product Knowledge, Corporate Image, Relationship Marketing, dan Trust terhadap Keputusan Menabung Nasabah di Bsi Kcp Jakarta Duri Kosambi (Wom Moderation) - Osly Usman; Fatimah Azzahra Hidayat (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze the influence of product knowledge, corporate image, relationship marketing, and trust on customers’ savings decisions at Bank Syariah Indonesia (BSI) KCP Jakarta Duri Kosambi, as well as examine the moderating effect of word of mouth in the relationship between these variables. The background of this research is based on the relatively low number of customers at BSI KCP Jakarta Duri Kosambi, which only reached 515 customers by the end of 2023, despite the large Muslim population in Cengkareng District, which represents a significant potential market for Islamic banking services. This study employs a quantitative research method using a questionnaire distributed to 100 customers selected through accidental sampling techniques. The data were analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS) with the assistance of SmartPLS 4.0 software. The results indicate that product knowledge, corporate image, relationship marketing, and trust each have a significant positive effect on savings decisions, as reflected in their respective path coefficients and t-statistics. Furthermore, word of mouth is found to significantly moderate only the relationship between relationship marketing and savings decisions, while its moderating effect on product knowledge, corporate image, and trust is not significant. These findings suggest that BSI KCP Jakarta Duri Kosambi should strengthen marketing strategies focusing on customer knowledge, institutional image, relationship quality, and trust to enhance customers’ savings decisions.